Murder at Mullings - Cannell, Dorothy (Severn House, 2014)
In its 300-year history, there has never once been a scandal at Mullings, ancestral home of the decent but dull Stodmarsh family. Until, that is, Edward Stodmarsh makes an ill-advised second marriage to the scheming Regina Stapleton, who insists on bringing her family's 'ornamental hermit' to live on the estate. Suddenly everyone wants to visit Mullings to glimpse this mysterious figure. Strange but harmless, thinks Florence Norris, the family's longstanding housekeeper. But events take a sinister turn with the arrival of sudden, violent death - and suddenly the hermit doesn't seem so harmless after all.